Literature Study of Self-Care and Self-Help Approaches in Increasing the Independence of Students with Intellectual Disability - Sunarwi, Taufik Wayan; Sunandar, Asep; Ummah, Umi Safiul; Ediyanto, Ediyanto (Jurnal ORTOPEDAGOGIA, 2025)
The skills for self-care and self-help should be taught to children, particularly for students with intellectual disability. This study aims to identify the influencing factors for self-care and self-help abilities in intellectually disabled children. The research employs a case study methodology, with observations conducted at PGRI Special School Bangorejo (PGRI Special Needs School of Bangorejo). In particular, the research identifies the rationale for seventh-grade special school students who are unable to perform self-care and self-help skills related to personal hygiene, such as bathing, brushing their teeth, and dressing independently. In light of these findings, the researcher has identified potential solutions to address the existing challenges, thereby enabling students to engage in self-development activities related to self-care and self-help, such as bathing, brushing their teeth, and dressing independently.